2022
DOI: 10.1007/s00217-022-04122-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extraction methods for active biomolecules using sub-critical dimethyl ether and n-butane

Abstract: Several extraction methods are used to isolate natural compounds, and recent approaches utilize subcritical or supercritical extraction media. In this paper we compare extraction methods based on subcritical eluents, dimethyl ether (sC-DME) and n-butane (sC-nB), under mild conditions, using coffee beans and powder as an exemplary raw material. The parameters to be controlled to improve the extraction are considered, and the resulting data discussed. The results obtained display higher selectivity of sC-DME for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The extract was obtained from the internal and external pomegranate peel, through an eco-sustainable extraction method with low environmental impact according to Ciulla et al [ 25 ]. The extraction of pomegranate peel was performed under two different conditions: Dimethyl Ether (DME) and n-butane.…”
Section: Methodsmentioning
confidence: 99%
“…The extract was obtained from the internal and external pomegranate peel, through an eco-sustainable extraction method with low environmental impact according to Ciulla et al [ 25 ]. The extraction of pomegranate peel was performed under two different conditions: Dimethyl Ether (DME) and n-butane.…”
Section: Methodsmentioning
confidence: 99%
“…Liquefied DME enables catechin extraction while completely removing caffeine. Ciulla et al also demonstrated higher extraction rates of caffeine from coffee beans and powder using liquefied DME rather than using scCO 2 -based extraction methods [184].…”
Section: Extraction Of Functional Components From Natural Resourcesmentioning
confidence: 99%